(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
Relevance The effectiveness of treating patients with penetrating wounds of the eyeball depends on the quality of specialized medical care. It includes a full scope of primary surgical treatment of the wound and adequate conservative, surgical treatment of post-traumatic inflammatory complications, professionally correct observation of patients with consequences of penetrating wounds of the eye. Outpatient observation of these patients is carried out mainly in polyclinics at the place of residence. Nevertheless, ophthalmologists of the polyclinic do not always have the opportunity (in terms of instrumental and laboratory equipment, availability of appropriate specialization) to competently assess the severity of the injury and the prognosis of the course of the post-traumatic period, and are not always competent in resolving issues of surgical rehabilitation of these patients.